Bi-atrial thrombosis in a patient with SARS-CoV-2 infection: a case report. Issue 6 (6th November 2020) - Torres, Ricardo; Gul, Fahad; Azmaiparashvili, Zurab; Patarroyo-Aponte, Gabriel
Abstract: Background: Coronavirus disease 2019 (COVID-19) is a rapidly spreading pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It is a multisystemic disease associated with micro- and macrovascular thrombo-embolic complications, including intracardiac thrombosis, which has not been previously reported in the literature. Case summary: We report a case of a 68-year-old woman with COVID-19 admitted to our intensive care unit with acute respiratory distress, undifferentiated shock, hyperkalaemia, acute kidney injury, and coagulopathy. She received crystalloid infusion, broad-spectrum antibiotics, hydroxychloroquine, insulin–dextrose, calcium gluconate, sodium bicarbonate, and i.v. vasopressors. Continuous renal replacement therapy (CRRT) was started for refractory hyperkalaemia and metabolic acidosis. Transthoracic echocardiogram obtained for concern of pulmonary embolism found bi-atrial thrombosis with normal bi-ventricular dimensions and function. Systemic anticoagulation was provided, but this was stopped soon afterwards due to worsening coagulopathy and bleeding. Despite intensive measures and supportive therapy, the patient developed worsening hypoxia, refractory shock, and multiorgan failure. After discussion of goals of care with her family, a decision was made to initiate hospice care. The patient died within 72 h of hospital admission. Discussion: Infection with SARS-CoV-2 is a multisystemic disease that primarily affects the lungs, but also predisposes to rare thrombo-embolic phenomena such as intracardiac thrombosis.